2023
DOI: 10.1007/s11033-023-08259-x
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PCAT6 promotes proliferation, migration, invasion, and epithelial-mesenchymal transition of lung adenocarcinoma cell by targeting miR-545-3p

Abstract: Background Lung cancer is a high incidence cancer on a worldwide basis and has become a major public health problem. Lung adenocarcinoma (LUAD) makes up approximately half of all lung cancers and is a threat to human health. Long non-coding RNAs (lncRNAs) is an important regulator of the development and progression of lung adenocarcinoma. In this manuscript we examined the role and potential mechanism of lncRNA PCAT6 in the development of LUAD. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Exosomal miR-181b-5p and let-7c-5p was found to inhibit the EMT process in BEAS-2B cells by modulating the MAPK signaling pathway, resulting in the enhancement of migratory and invasive ability in BEAS-2B cells (84). Moreover, Yang et al showed that lncRNA PCAT6 significantly repressed the migration, invasion, and EMT of A549 and H1975 cells by increasing EGFR expression via sequestering miR-545-3p (131). Liu et al revealed that circSCN8A suppressed invasion, metastasis, and EMT in NSCLC cell lines.…”
Section: Ncrna In Lc Invasion and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomal miR-181b-5p and let-7c-5p was found to inhibit the EMT process in BEAS-2B cells by modulating the MAPK signaling pathway, resulting in the enhancement of migratory and invasive ability in BEAS-2B cells (84). Moreover, Yang et al showed that lncRNA PCAT6 significantly repressed the migration, invasion, and EMT of A549 and H1975 cells by increasing EGFR expression via sequestering miR-545-3p (131). Liu et al revealed that circSCN8A suppressed invasion, metastasis, and EMT in NSCLC cell lines.…”
Section: Ncrna In Lc Invasion and Metastasismentioning
confidence: 99%
“…EMT is a biological process of cellular morphological alterations in which epithelial cells obtain mesenchymal characteristics. Recent studies suggest that ncRNA dysregulation endows LC cells with invasive and metastatic characteristics by altering EMT (84,131,132). Exosomal miR-181b-5p and let-7c-5p was found to inhibit the EMT process in BEAS-2B cells by modulating the MAPK signaling pathway, resulting in the enhancement of migratory and invasive ability in BEAS-2B cells (84).…”
Section: Ncrna In Lc Invasion and Metastasismentioning
confidence: 99%
“…Yang et al. ( 45 ) found that LncRNA PCAT6 promotes proliferation, migration, invasion, and epithelial-mesenchymal transition of lung adenocarcinoma cells by targeting miR-545-3p. Zhong et al.…”
Section: The Regulation Of Signaling Pathway That Lncrna Participated...mentioning
confidence: 99%
“…Wang et al (44) found that LncRNA FBXL19-AS1 induces tumor growth and metastasis by sponging miR-203a-3p in lung adenocarcinoma. Yang et al (45) found that LncRNA PCAT6 promotes proliferation, migration, invasion, and epithelial-mesenchymal transition of lung adenocarcinoma cells by targeting miR-545-3p. Zhong et al (46) found that LncRNA TTN-AS1 drives the invasion and migration of lung adenocarcinoma cells via modulation of miR-4677-3p/ZEB1 axis.…”
Section: Mirna Signaling Axis 581 Mirna-3pmentioning
confidence: 99%
“…Studies identified the dual role of lncRNAs by interacting various signal pathways in LUAD. Some lncRNAs promoted the progression of LUAD, such as lncRNA PCAT6 by sponging miR-545-3p and lncRNA FOXD2-AS1 by regulating cell cycle ( 18 , 19 ). However, some lncRNAs inhibited the progression of LUAD, such as lncRNA SNHG5 by regulating epithelial-mesenchymal transition and lncRNA HITT by attenuating Rab5-mediated endocytosis ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%